Nr4a1 is required for fasting-induced down-regulation of Pparγ2 in white adipose tissue - Duszka, Kalina; Bogner-Strauss, Juliane G; Hackl, Hubert; Rieder, Dietmar; Neuhold, Claudia; Prokesch, Andreas; Trajanoski, Zlatko; Krogsdam, Anne-M (Molecular endocrinology (Baltimore, Md.), 2013)
Expression of the nuclear receptor gene, Nur77 (Nr4a1), is induced in white adipose tissue (WAT) in response to β-adrenergic stimulation and fasting. Recently, Nur77 has been shown to play a gene regulatory role in the fasting response of several other major metabolic tissues. Here we investigated the effects of Nur77 on the WAT transcriptome after fasting. For this purpose, we performed gene expression profiling of WAT from wild-type and Nur77(-/-) mice submitted to prolonged fasting. Results revealed Nur77-dependent changes in expression profiles of 135 transcripts, many involved in insulin signaling, lipid and fatty acid metabolism, and glucose metabolism. Network analysis identified the deregulated genes Pparγ2 and Nur77 as central hubs and closely connected in the network, indicating overlapping biological function. We further assayed the expression level of Pparγ2 in a bigger cohort of fasted mice and found a significant Nur77-dependent down-regulation of Pparγ2 in the wild-type mice (P = 0.021, n = 10). Consistently, the expression of several known Pparγ2 targets, found among the Nur77-regulated genes (i.e. G0s2, Grp81, Fabp4, and Adipoq), were up-regulated in WAT of fasted Nur77(-/-) mice. Finally, we show with chromatin immunoprecipitation and luciferase assays that the Pparγ2 promoter is a direct target of Nurr-related 77-kDa protein (Nur77)-dependent repressive regulation and that the N-terminal domain of Nur77 is required for this regulation. In conclusion, we present data implicating Nur77 as a mediator of fasting-induced Pparγ2 regulation in WAT.